Integration examinations for regular migrants: the difficult search for a balance between national competencies and full effectiveness of EU law - Montaldo, Stefano (2016)
According to Article 79(4) TFEU, integration policies fall under the competence of the Member States, while the EU plays a complementary role. However, the EU has been exercising an increasing influence in this domain: on the one hand, the Commission launched a series of policy initiatives, under the common umbrella of a European Integration Agenda, aiming at coordinating national efforts and best practices; on the other hand, integration clauses were included in some secondary acts concerning regular migration. In this context, Directive 2003/109/EC on long-term residents and Directive 2003/86/EC on family reunification allow Member States to require third country nationals to comply with integration conditions or measures, which often take the shape of basic integration exams. In particular, the enjoyment of the rights conferred by these Directives is often made conditional upon the fulfillment of the integration requirements. The Court of Justice of the European Union (henceforth, CJEU) has recently confirmed these examinations to be compatible with EU law; however, the organization and the contents of these examinations must pass a strict proportionality test. In fact, they must not result in tools to select migrants, rather to favour the integration of third country nationals regularly settled in the hosting States.